Dosimetric effects and impacts caused by a carbon fiber table and its accessories in a linear accelerator - Alabedi , Haydar H.; Al Musawi , Mustafa S.; Mohammed Ali , Nabaa (Journal of Contemporary Medical Sciences, 2023)
Objective : Most contemporary treatment planning systems (TPS) exclude the couch during treatment planning. The present investigation aimed to evaluate the impact of couches and accessories on radiation therapy planning by quantifying the degree of attenuation for two-photon beam energies, 6 MV and 10 MV, at two different field sizes, 5 cm x 5 cm and 10 cm x 10 cm. Methods: An x-ray radiation beam at two energies (6 MV and 10 MV) generated by a linear accelerator (Elekta Synergy). The output dose was measured using a digital parallel plate ionization chamber of the IBA cc13 type (IBA Dosimetry, Germany), and the readings were recorded with a 2944 Farmer Type chamber. Different commercially available couch tops and accessories evaluated in this study. Results: The results show that the highest attenuation values were observed at 1300 gantry angles for both energies and field sizes. The lowest attenuation values were recorded at 1000 gantry angles with 6 MV energy for 5cm x 5cm and 10cm x 10cm field sizes. The breast board with D level demonstrated the highest attenuation of 6.27% and 5.51% for 6 MV and 10 MV energies, respectively. Conclusion: the findings indicate that the degree of attenuation is not uniform across all angles and may exceed tolerable limits, indicating the need for careful consideration during treatment planning to ensure optimal treatment outcomes.